Normal Atmospheric Oxygen Tension and the Use of Antioxidants Improve Hepatocyte Spheroid Viability and Function - Lillegard, Joseph B. (2011)
BACKGROUND: Hepatocyte spheroids have been proposed for drug metabolism studies and in bioartificial liver devices. However, the optimal conditions required to meet the aerobic demands of mitochondria-rich hepatocyte spheroids is not well studied. We hypothesized that an optimal concentration of oxygen could be identified and that the health of hepatocyte spheroids might be further improved by antioxidant therapy. METHODS: Rat hepatocyte spheroids were maintained in suspension culture for 7 days under a mixture of 5% CO(2) plus O(2):N(2) to achieve fractional oxygen contents of 6% (C1), 21% (C2), 58% (C3), 95% (C4). Spheroid health was assessed under each condition by vital staining, TEM, oxygen consumption and mitochondrial counts. Hepatocyte differentiation was assessed by expression of ten liver-related genes (HNF4a, HNF6, Cyp1A1, albumin, Nags, Cps1, Otc, Ass, Asl, Arg1). Functional markers (albumin and urea) were measured. The influence of oxygen tension and antioxidant treatment on the production of reactive oxygen species was assessed by confocal microscopy. RESULTS: We observed that the hepatocyte spheroids were healthiest under normal atmospheric (C2) conditions with antioxidants ascorbic acid and L-carnitine. Cell death and reduced functionality of hepatocyte spheroids correlated with the formation of reactive oxygen species. CONCLUSION: Normal atmospheric conditions provided the optimal oxygen tension for suspension culture of hepatocyte spheroids. The formation and deleterious effects of reactive oxygen species were further reduced by adding antioxidants to the culture medium. These findings have direct application to development of the spheroid reservoir bioartificial liver and the use of hepatocyte spheroids in drug metabolism studies.